Estrogen Receptor, Progesterone Receptor, and HER-2 Expression in Recurrent Pleomorphic Adenoma - Ana Amélia de Souza; Albina Altemani; Ney Soares de Araujo; Lucas Novaes Texeira; Vera Cavalcanti de Araújo; Andresa Borges Soares (SAGE Publishing, 2019)
Pleomorphic adenoma (PA) is the most common salivary gland neoplasm and, although mostly benign, recurrences, being called recurrent pleomorphic adenoma (RPA) and malignant transformation to carcinoma ex pleomorphic adenoma (CXPA), do occur. Recently, attention has been focused on molecular targeted cancer therapy in various tumors, including salivary gland tumors. The aim of this study was to investigate the role of estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor-2 (HER-2) in PA, RPA, and CXPA. In total, 20 cases of PA, 18 of RPA, and 7 cases of CXPA were immunohistochemically studied for ER, PR, and HER-2. For evaluation of ER and PR, only nuclear expression and greater than 10% positive cells were regarded as cutoff criteria. HER-2 was evaluated semiquantitatively and graded from 0 to 3+. HER-2 amplification was assessed by chromogenic in situ hybridization (CISH). Tumors were negative for ER, PR, and HER-2 in all cases of PA and RPA. A case of CXPA showed moderate and complete membranous staining, and 6 cases were negative. HER-2 amplification was not observed in any case. In conclusion, the lack of ER, PR, and HER-2 expression in PA, RPA, and CXPA suggests that these proteins are not involved in progression, recurrence, or malignant transformation of PA.